Politics, Polarity, and Peace - Barnes, Will (Religious Studies, Theology and Philosophy E-Books Online, Collection 2023., 2023)
The arguments within the contemporary literature paint a clear picture: popular discourse is marked with extreme partisanship and polarization, threatening democracy, tolerance, diversity, pluralism, and cooperation. Polarization simplifies and deforms language, ideas, and people. Polarization reduces the complexities of social life into an oppositional binary based on crude distinctions revolving around partial and harmful reified conceptions of self and other. Since the egocentric ''us versus them" narratives catalyze conflicts which tend to violence, polarization is itself a cause of violence. The project of peace, then, is aided by the project of depolarization. But what can we do to bring about a transformation away from polarity to peace? What are the real polarities obscuring the path to peace? Is it a question of freedom versus control? Is it one of absolutism versus open-mindedness? Is it good versus evil? In a time of increasingly poisonous national politics, widening tribal polarity, and fragmented and fragmenting communities, what sense does it even make to appeal to reason, discourse, and compromise? The authors in this volume attempt to answer these and other questions relating to polarity and politics in the pursuit of peace and justice, the guiding ideals of the Concerned Philosophers for Peace and Brill's Philosophy of Peace series. .